First record of Steindachnerina insculpta (Fernández-Yépez, 1948) (Characiformes, Curimatidae) in Argentina - Aguilera, Gaston (2018)
Recent expeditions to northwestern Argentina revealed the presence of an unknown species of Curimatidae for the Bermejo river basin. The morphometric and meristic analyses of these specimens allow us to identify them as Steindachnerina insculpta (Fernández-Yépez, 1948), which is here reported for the first time in Argentina.